2023
DOI: 10.2298/tsci221014066d
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study results of the front-end device with two-tier air burner as part of the gas turbine engine combustion chamber

Abstract: In recent years, the gas turbine power plant has been increasingly used in various industries in Kazakhstan. The reasons for this are: thermal efficiency; simplicity of the thermal scheme and design; small mass per power unit; high maneuverability; low toxicity; relatively simple automation of operation. This paper presents the experimental study results of a two-tier air burner as the part of the gas turbine engine combustion chamber at burning liquid fuel. ? new design of a microflame devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…As the angle increases to 45 • , the stabilization characteristics noticeably improve. Previous studies in the field of burner devices with variable blade positions [35] have shown that, from the perspective of flame stabilization and the generation of toxic substances, an angle of 45 • is the most optimal. This effect occurs because, at this specific angle, the most effective recirculation zone is created, primarily in the central part of the burner.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the angle increases to 45 • , the stabilization characteristics noticeably improve. Previous studies in the field of burner devices with variable blade positions [35] have shown that, from the perspective of flame stabilization and the generation of toxic substances, an angle of 45 • is the most optimal. This effect occurs because, at this specific angle, the most effective recirculation zone is created, primarily in the central part of the burner.…”
Section: Resultsmentioning
confidence: 99%
“…During the experiment, the vanes were positioned at 30°, 40°, and 60° relative to the burner axis. According to previous studies, the most optimal inner vanes angle is 45° [35]. For the study, three vane angles were taken, which varied along the burner axis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation